2004
DOI: 10.1080/03079450400013188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic hypoxia during embryonic development on physiological functioning and on hatching and post-hatching parameters related to ascites syndrome in broiler chickens

Abstract: The present study was designed to investigate the effect of different atmospheric pressure on the endogenous functions of broiler chickens during embryonic, hatching and growing periods related to ascites. Eggs from a commercial broiler line were incubated in two similar commercial incubators at high and low altitudes. The effect on embryonic development and physiological functions including hatching parameters, incidence of ascites and growth performance were examined. Embryos incubated at high altitude had h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
40
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 28 publications
(41 reference statements)
9
40
2
2
Order By: Relevance
“…The O 2 supplementation at high altitude did not affect the live weight of broilers compared with the HA group except at days 7, 28 and 35. The results of the present study are in contrast with those of Hassanzadeh et al (2004), Bahadoran et al (2010) and Çelen et al (2009), who showed that high-altitude incubated chickens had significantly higher bodyweights than low-altitude incubated chickens at 42 days old. In contrast to our findings, Meshew (1949) and Wilgus & Sadler (1954) report a slightly heavier weight at 2 and 3 weeks old when O 2 was added.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The O 2 supplementation at high altitude did not affect the live weight of broilers compared with the HA group except at days 7, 28 and 35. The results of the present study are in contrast with those of Hassanzadeh et al (2004), Bahadoran et al (2010) and Çelen et al (2009), who showed that high-altitude incubated chickens had significantly higher bodyweights than low-altitude incubated chickens at 42 days old. In contrast to our findings, Meshew (1949) and Wilgus & Sadler (1954) report a slightly heavier weight at 2 and 3 weeks old when O 2 was added.…”
Section: Discussioncontrasting
confidence: 99%
“…However, O 2 supplementation at high altitude did not affect feed consumption and FCR. In contrast to our findings, Hassanzadeh et al (2004) and Bahadoran et al (2010) found that there were no differences between the feed intakes of the high-altitude and low-altitude incubated groups during the growing period, and FCR was found to be lower in the high-altitude incubated group than low-altitude incubated group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, environmental causes such as altitude, cold stress and rearing conditions such as feed, lighting, air quality and ventilation have all been implicated in the development of pulmonary hypertension (Hassanzadeh et al, 2005;Baghbanzadeh and Decuypere, 2008). It has been reported that chronic hypoxia interacting with the endogenous functions of embryos during embryonic development at high altitude, as adaptation mechanisms, changed the developmental trajectories of cardiopulmonary parameters in postnatal chickens, thus lowering their susceptibility to pulmonary hypertension (Hassanzadeh et al, 2004;Hassanzadeh et al, 2008), while hypoxia could cause the growing broiler to become more susceptible to pulmonary hypertension (Baghbanzadeh and Decuypere, 2008). The incidence of pulmonary hypertension has been reported to be greatly increased at altitudes higher than 1300 metres above sea level, presumably because of low oxygen concentration (Hernandez, 1987).…”
mentioning
confidence: 99%